Myricanol mitigates lipid accumulation in 3T3-L1 adipocytes and high fat diet-fed zebrafish via activating AMP-activated protein kinase. (1st January 2019) - Shen, Shengnan; Liao, Qiwen; Feng, Yu; Liu, Jingxin; Pan, Ruile; Lee, Simon Ming-Yuen; Lin, Ligen
Highlights: Myricanol from the barks of Chinese bayberry was identified as an AMPK activator. Myricanol inhibited adipogenesis in the initial stage of adipocytes differentiation. Myricanol induced lipolysis and lipid oxidation in 3T3-L1 adipocytes. Myricanol improved insulin sensitivity in mature adipocytes. Myricanol attenuated lipid accumulation in high-fat diet-fed zebrafish. Abstract: Myricanol is a diarylheptanoid isolated from Chinese bayberry. Through virtual docking strategy, myricanol was discovered as an AMP-activated protein kinase (AMPK) activator among a series of structural analogs, with high affinity for the γ subunit of AMPK. Myricanol was also evaluated for regulatory effects on lipid accumulation and insulin sensitivity in 3T3-L1 adipocytes and adiposity in high-fat diet-fed zebrafish. Myricanol suppressed lipid accumulation in 3T3-L1 cells in the initial stage (days 0–2) by suppressing adipogenesis and in the terminal stage (days 4–7) by inducing lipolysis and lipid combustion through activating AMPK. Moreover, myricanol enhanced insulin-stimulated glucose uptake by activating the insulin signaling pathway. In high-fat diet-fed zebrafish, myricanol inhibited lipid accumulation by suppressing adipogenic factors including peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα). In summary, the results indicate that myricanol could be a potential therapeutic agent against obesity by activating the AMPK signaling pathway.